Use of amniotic membrane in the treatment of patients with BRONJ: two case reports - Ragazzo, Mirko (J Surg Case Rep, 2018)
The use of bisphosphonates has led to a new disease, bisphosphonate-related osteonecrosis of the jaw (BRONJ). There is currently no effective treatment for this disease; the surgical approach is controversial. The widespread use of human amniotic membrane (HAM) in surgery and the results obtained have highlighted its many potential properties, including antimicrobial, anti-inflammatory, antifibrotic and antiapoptotic, as well as its capacity for encouraging epithelialisation and cell differentiation. These properties are believed to encourage the recovery of patients with BRONJ, facilitating the wound healing process after surgical debridement of the bone. We report our experience with the use of HAM: two patients treated with patches of HAM. The follow-up to date, which includes x-rays and clinical assessments, demonstrates good levels of epithelialisation and absence of infections and pain. To conclude, the use of HAM in patients with BRONJ seems to be a promising therapeutic alternative to current conventional treatments.